2015
DOI: 10.1021/acs.jpcb.5b06838
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of Oligopeptide Containing Poly(ethylene glycol) Brushes for Stimuli-Responsive Drug Delivery

Abstract: Stimuli-responsive biomaterials are used to facilitate drug and gene delivery by shielding the drug/gene during circulation times and selectively releasing the cargo at the desired target. Within stimuli-responsive materials, pH-responsive materials are exploited for delivery to specific organs, intracellular compartments, cancer cells, site of inflammation or infection as those sites are characterized by pH that is different from the blood pH. In this paper we use molecular dynamics (MD) simulations to design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Simulations with atomistic models are used for characterizing (a) specific atomic-level interactions in a known morphology, (b) intermolecular interactions within the chain and between the chain and solvent/additive/ion that stabilize a secondary structure or crystalline state of the polymer, (c) interactions between two polymers that bind/complex together, and so forth. For example, in our group, we have used atomistic (or all-atom) models to describe interactions between two charged polymers where one or both have a known secondary structure, to understand how poly­(ethylene glycol) conjugated to polypeptides impacts the polypeptide conformations, to understand how solvent (water) interacts with an elastin-like peptide chain to drive its phase transition, and so forth. In all of these cases, we either did not know a priori the key molecular driving forces for the systems at hand, and hence did not have the insight to develop coarser models (like those in section ), or had scientific objectives that necessitated this level of chemical detail.…”
Section: “What Model Should I Use For the Problem At Hand?”mentioning
confidence: 99%
“…Simulations with atomistic models are used for characterizing (a) specific atomic-level interactions in a known morphology, (b) intermolecular interactions within the chain and between the chain and solvent/additive/ion that stabilize a secondary structure or crystalline state of the polymer, (c) interactions between two polymers that bind/complex together, and so forth. For example, in our group, we have used atomistic (or all-atom) models to describe interactions between two charged polymers where one or both have a known secondary structure, to understand how poly­(ethylene glycol) conjugated to polypeptides impacts the polypeptide conformations, to understand how solvent (water) interacts with an elastin-like peptide chain to drive its phase transition, and so forth. In all of these cases, we either did not know a priori the key molecular driving forces for the systems at hand, and hence did not have the insight to develop coarser models (like those in section ), or had scientific objectives that necessitated this level of chemical detail.…”
Section: “What Model Should I Use For the Problem At Hand?”mentioning
confidence: 99%
“…Yet, its reliability depends on the adequate choice of essential degrees of freedom (i.e., electronic, nuclear, atomic, and molecular) and of interaction potentials (i.e., quantum or classical mechanics) governing the motion along these degrees of freedom . Different levels of coarse-grained representations have been successfully combined with MD simulations to investigate the structural and thermodynamic properties of conventional polymer brushes. However, fewer systematic studies have reported on atomistic MD simulations of polymer brushes. These reports have demonstrated the requirement of an atomic description to properly account for the role of a solvent on polymer chain dynamics and interactions, and ion-specific effects on the structure, mechanics, and interfacial softness of polymer brushes. Moreover, reliable coarse-grained models are expected to reproduce molecular properties of the underlying atomistic system so that accurate atomistic models are also necessary for the development of robust coarse-grained (CG) models . Furthermore, the properties of strong and weak polyelectrolyte brushes have been extensively investigated via continuum models based on the scaling , and self-consistent field theories.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer grafted nanoparticles are a class of hybrid materials where organic/inorganic nanoparticles are functionalized with synthetic polymers or biopolymers that are tethered/anchored at a desired grafting density. These hybrid materials have been the topic of many computational and experimental studies in the past decade that have focused on the synthesis of these polymer grafted nanoparticles, on their structural characterization in solution, melts, and in polymer matrix, and on their use in a myriad of applications. These applications include, but are not limited to, the use of polymer grafted particles as fillers in polymer nanocomposites, their assembly into optically active materials, their role as compatibilizers in fluid–fluid interfaces, and their use as carriers for drugs/other cargo in biomedical applications. The majority of these past studies have emphasized the role of polymer grafted particles as fillers in nanocomposites linking the effects of grafted polymer chemistry, molecular weight, grafting density to the grafted layer structure, and filler dispersion/aggregation/ordering as a function of particle chemistry, particle size, medium (solvent/matrix) chemistry, and molecular weight. , , In particular, these studies have established the fundamental rules emphasizing the role of the grafted layer in dictating the enthalpic and entropic driving forces behind wetting/mixing of the medium (solvent/matrix polymer) with the grafted chains.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their use in nanocomposites, polymer grafted particles have also been used in biomedical applications as imaging or delivery agents. When used for imaging, the particle itself serves as the imaging agent with the grafted layer providing a stealth coverage. When used for biological delivery, the functional biomolecule/drug could either be loaded in the grafted layer or be the particle itself, with the grafted biocompatible polymers (e.g., poly­(ethylene glycol)) protecting/shielding the drug(s) during circulation in both cases.…”
Section: Introductionmentioning
confidence: 99%